Application of extracorporeal shock wave therapy in nervous system diseases: A review - Guo, Juan; Hai, Hong; Ma, Yuewen (Frontiers in Neurology, 2022)
Neurological disorders are one of the leading causes of morbidity and mortality worldwide, and their therapeutic options remain limited. Recent animal and clinical studies have shown the potential of extracorporeal shock wave therapy (ESWT) as an innovative, safe, and cost-effective option to treat neurological disorders. Moreover, the cellular and molecular mechanism of ESWT has been proposed to better understand the regeneration and repairment of neurological disorders by ESWT. In this review, we discuss the principles of ESWT, the animal and clinical studies involving the use of ESWT to treat central and peripheral nervous system diseases, and the proposed cellular and molecular mechanism of ESWT. We also discuss the challenges encountered when applying ESWT to the human brain and spinal cord and new potential applications of ESWT in treating neurological disorders.